Empire, religion, and identity: modern South Asia and the global circulation of ideas - Mukherjee, Soumen (Brill's Indological library, 2024)
"This collection brings together case studies that cover a wide spectrum: from Hindu, Buddhist, Jaina traditions through reformist ventures such as the Brahmos, to issues in modern Islam and Judaism. The first part of the book explores idioms of self-fashioning in global platforms and religious congresses. The second part explicates the nature of movements of such ideas. Cumulatively, they offer fresh and invaluable insights into their histories in modern South Asia against the backdrop of, and in relation to, wider transcultural global flows"--